Spirit of terrorism or war, which was not (Jean Baudrillard) (Journal of Philosophy Culture and Political Science, 2018)
Article is devoted terr act in the city of Moscow the Domodedovo airport that involves cardinal revaluation of values of the person and its motivational promptings, concerning understanding of life as granted of explicating lives and human nature ontologies.